2008
DOI: 10.1073/pnas.0710626105
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human monoamine oxidase A at 2.2-Å resolution: The control of opening the entry for substrates/inhibitors

Abstract: The mitochondrial outer membrane-anchored monoamine oxidase (MAO) is a biochemically important flavoenzyme that catalyzes the deamination of biogenic and xenobiotic amines. Its two subtypes, MAOA and MAOB, are linked to several psychiatric disorders and therefore are interesting targets for drug design. To understand the relationship between structure and function of this enzyme, we extended our previous low-resolution rat MAOA structure to the high-resolution wild-type and G110A mutant human MAOA structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
475
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(493 citation statements)
references
References 24 publications
12
475
0
6
Order By: Relevance
“…/HOO Ϫ . This role has been assigned to a His in glucose oxidase (12,32) and to a Lys in monomeric sarcosine oxidase (36) and in monoamine oxidase (37,38). In DAAO, this would be implemented by the proposed H ϩ relay system.…”
Section: Discussionmentioning
confidence: 99%
“…/HOO Ϫ . This role has been assigned to a His in glucose oxidase (12,32) and to a Lys in monomeric sarcosine oxidase (36) and in monoamine oxidase (37,38). In DAAO, this would be implemented by the proposed H ϩ relay system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a full-length crystal structure of the human MAOA is available (Protein Data Bank 2Z5Y, from positions 12-524 out of 527 aa). 37 The analysis of the modeled 3D structure by the prediction program KD4v indicates that the missense affects an aminoacid in a beta sheet close to the FAD-binding pocket, and the bulky aromatic ring of phenylalanine is oriented toward the FAD-binding pocket (Figure 1e), which may explain the observed effect on enzymatic activity (see below). We also genotyped the VNTR located in the MAOA promoter and observed that the proband III-1 carries the 3R (three repeats) allele, associated with 'low expression' of MAOA, 13 which may thus potentiate the effect of the missense mutation on the level of MAOA activity.…”
Section: Cognition and Behavioral Disorder A Piton Et Almentioning
confidence: 99%
“…Its structure is closely related to pargyline which has a slight selectivity for MAO-B. The reason for this difference in selectivity can be explained by the 3-dimentional structure of the enzymes and caused by the structural differences arising from Ile-335 in MAO-A versus Tyr-326 in MAO constraining the access to the active centre and limiting the access of clorgiline (Son, 2008). Clorgiline was never marketed but used as tool in scientific research and further search for selective MAO-A inhibitors finally cumulate in the discovery of reversible and selective inhibitors of MAO-A also known as RIMAs.…”
Section: Irreversible Selective Mao-a Inhibitorsmentioning
confidence: 99%